2019
DOI: 10.1063/1.5079707
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subcavity in supersonic cavity flow

Abstract: An experimental and numerical study is conducted on a rectangular open cavity with a length to depth ratio of 2 at Mach number 1.71 by placing a subcavity at different locations. The subcavity at the front wall has already been established as a passive control device experimentally. In addition, it has been observed that it can act as a passive resonator. However, in the current study, it is found that the location of the subcavity and its dimensions play a crucial role in determining the types of oscillations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…And this minimum pressure can result in positive or negative pressure as Mach number changes, which result positive or negative coefficient of pressure (C p ) at different location of the cavity. Negative pressure coefficient distribution across the cavity can result in decrease in drag [21].…”
Section: Open Cavitymentioning
confidence: 99%
“…And this minimum pressure can result in positive or negative pressure as Mach number changes, which result positive or negative coefficient of pressure (C p ) at different location of the cavity. Negative pressure coefficient distribution across the cavity can result in decrease in drag [21].…”
Section: Open Cavitymentioning
confidence: 99%
“…Measurements are taken at different locations. Unsteady statistics are collected in particular at three probing locations along the cavity wall ([s/D] = 0.25, 2, 3.75), which are later utilized to understand the flow physics and also to compare with the findings of Panigrahi et al 20 . Two streamwise rakes extending between −1 ≤ [x/D] ≤ 3 are placed at differed transverse locations ([y/D] =0, and 0.5) in the freestream to understand the influence of cavity dynamics on the shock oscillations.…”
Section: A Geometrical Configurationmentioning
confidence: 99%
“…Confined supersonic stream is encountered in variety of gas-dynamic scenarios including flow through ducts [1][2][3][4] , overexpanded nozzles [5][6][7] , isolator of scram-jet inlets [8][9][10][11] , enclosed open jet wind-tunnels [12][13][14] , and ejectors [15][16][17][18] , where the influence of nearby walls on the quality of flow is substantial. One among such a flow field is supersonic flow past a confined cavity [19][20][21][22] . Mixed-compression inlet for shock-wave boundary layer control 23,24 , resonator type supersonic nozzles 25,26 , gas-dynamic lasers 27,28 , and scram-jet combustors 29,30 often employ cavities in supersonic flow which are placed in closed proximity to the surrounding walls.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies [17][18][19] showed that using a cavity after the injector significantly improves the combustion efficiency in a supersonic flow. The effect of sub-cavity in a supersonic cavity flow was studied by Panigrahi et al [20], who noted that the sub-cavity mitigates the shear layer reattachment at the aft wall of the cavity.…”
Section: Introductionmentioning
confidence: 99%